COUNSELING IN INCREASING HEALTH LITERACY CONCERNING KNOWLEDGE ON ADOLESCENT REPRODUCTIVE HEALTH IN JAKARTA - Ni Nyoman Sri Artina Dewi; Agustina ida Pratiwi (SEAJOM: The Southeast Asia Journal of Midwifery, 2020)
Health literacy is a very important part in increasing adolescent knowledge about reproductive health. This can be directed, one of them, by counseling. With various problems experienced by adolescents, this study aimed to see whether counseling given to adolescents in an area in central Jakarta, Indonesia, could provide significant results. This pre-experimental study recruited 28 adolescents to be given pretest and posttest with the theme of adolescent reproductive health. With validity and reliability tests conducted, the teenagers were given a questionnaire about reproductive health between the pretest and posttest, with intervention given in the form of counseling between the two tests. The results shown were that there was a significant difference between pretest and posttest done by the respondents after counseling was given to increase reproductive health literacy with a value of p <0.05.